2019
DOI: 10.1088/1742-6596/1256/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Wake characteristics of pumping mode airborne wind energy systems

Abstract: Airborne wind energy is an emerging technology that aims at harvesting wind power at high altitudes. In the present work, we propose a framework combining optimal control and large-eddy simulation to investigate the wake characteristics of large-scale airborne wind energy systems. We consider systems operating in pumping mode which alternate between power-generating and -consuming phases. We investigate the downstream wake development in non-turbulent and turbulent sheared inflow conditions. The optimal system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Due to the large size of the swept area of the kite trajectory -typically an annulus or a lemniscate on the spherical surface around the ground station -AWE systems typically lead to lower induction effects than conventional wind turbines. However, induction effects are particularly relevant for the optimization of multiple kite systems (De Schutter, Leuthold, Bronnenmeyer, Paelinck, & Diehl, 2019;Zanon, Gros, Andersson, & Diehl, 2013), and their inclusion into modeling and optimal control of AWE systems is the subject of ongoing research (Haas, De Schutter, Diehl, & Meyers, 2019;Leuthold et al, 2017;Trevisi, Gaunaa, & McWilliam, 2020).…”
Section: Fundamental Principles and Aerodynamic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large size of the swept area of the kite trajectory -typically an annulus or a lemniscate on the spherical surface around the ground station -AWE systems typically lead to lower induction effects than conventional wind turbines. However, induction effects are particularly relevant for the optimization of multiple kite systems (De Schutter, Leuthold, Bronnenmeyer, Paelinck, & Diehl, 2019;Zanon, Gros, Andersson, & Diehl, 2013), and their inclusion into modeling and optimal control of AWE systems is the subject of ongoing research (Haas, De Schutter, Diehl, & Meyers, 2019;Leuthold et al, 2017;Trevisi, Gaunaa, & McWilliam, 2020).…”
Section: Fundamental Principles and Aerodynamic Considerationsmentioning
confidence: 99%
“…When this physical phenomenon, abbreviated as the induction effect, is not included in AWE OCPs, the conversion efficiency does tend towards unity, as in . However, when (Haas et al, 2019) flies OCP-generated lift-mode trajectories within an atmospheric large-eddy-simulation (a high-fidelity induction model), the resulting induction effects are far too large to be safely neglected. Second, (Leuthold et al, 2017;Zanon, Gros, Meyers, & Diehl, 2014) find that the inclusion of a quasi-steady actuator model (a very rough induction model) into an OCP leads to a large drop in predicted power.…”
Section: Some Open Modeling Questions In Awe Optimal Controlmentioning
confidence: 99%
“…For a more detailed description of the model and the optimization algorithm see [135,84,29,19,71,67].…”
Section: Model Overviewmentioning
confidence: 99%
“…For individual systems, recent investigations of flow induction and wake effects were performed, mainly considering axissymmetric AWES configurations in uniform inflows using either analyses based on momentum theory (Leuthold et al, 2017;De Lellis et al, 2018), vortex theory (Leuthold et al, 2019;Gaunaa et al, 2020) or the entrainment hypothesis (Kaufman-Martin et al, 2021), or high-fidelity CFD simulations (Haas and Meyers, 2017;Kheiri et al, 2018). Further numerical investigations of large-scale airborne wind energy systems in the atmospheric boundary layer (ABL) (Haas et al, 2019b) have shown that the wake development downstream of the system is considerable, hence suggesting that wake effects of utility-scale airborne wind energy systems can not be neglected when operating in parks.…”
Section: Introductionmentioning
confidence: 99%